ReCOMmendations for the treatment of INFLUENZA in children for Primary care physiciAnS – COMPAS INFLUENZA - Doniec, Zbigniew; Mastalerz-Migas, Agnieszka; Jackowska, Teresa; Kuchar, Ernest; Sybilski, Adam (Family Medicine & Primary Care Review, 2019)
Influenza is an acute infectious disease of the airways that occurs in every age group. The course of the disease may have a different severity and clinical picture, from asymptomatic to severe with symptoms of respiratory failure. The possibilities of pandemic infections and serious complications throughout the course of influenza distinguish it from other viral respiratory diseases, prompting us to treat it in a special way. Diagnosis of the disease is usually clinical in nature, and additional studies may be helpful in clinically relevant cases. The drug recommended for treatment and chemoprophylaxis is oseltamivir. Clinical benefits are greatest if treatment starts as early as possible, within 48 hours of the first symptoms of influenza. Clinical studies indicate that early treatment with oseltamivir may shorten the duration of the disease and reduce the risk of its complications. Annual influenza vaccination is the most effective method of preventing this disease, and the only contraindication to vaccination is the occurrence of an anaphylactic or other severe allergic reaction after a previous vaccination.